Inside the Thrombus: Association of Hemostatic Parameters With Outcomes in Large Vessel Stroke Patients - Marta-Enguita, Juan; Navarro-Oviedo, Manuel; Muñoz, Roberto; Olier-Arenas, Jorge; Zalba, Guillermo; Lecumberri, Ramon; Mendioroz, Maite; Paramo, Jose A.; Roncal, Carmen; Orbe, Josune (Frontiers in Neurology, 2021)
Background: Actual clinical management of ischemic stroke (IS) is based on restoring cerebral blood flow using tissue plasminogen activator (tPA) and/or endovascular treatment (EVT). Mechanical thrombectomy has permitted the analysis of thrombus structural and cellular classic components. Nevertheless, histological assessment of hemostatic parameters such as thrombin-activatable fibrinolysis inhibitor (TAFI) and matrix metalloproteinase 10 (MMP-10) remains unknown, although their presence could determine thrombus stability and its response to thrombolytic treatment, improving patient's outcome. Methods: We collected thrombi (n = 45) from large vessel occlusion (LVO) stroke patients (n = 53) and performed a histological analysis of different hemostatic parameters [TAFI, MMP-10, von Willebrand factor (VWF), and fibrin] and cellular components (erythrocytes, leukocytes, macrophages, lymphocytes, and platelets). Additionally, we evaluated the association of these parameters with plasma levels of MMP-10, TAFI and VWF activity and recorded clinical variables. Results: In this study, we report for the first time the presence of MMP-10 and TAFI in all thrombi collected from LVO patients. Both proteins were localized in regions of inflammatory cells, surrounded by erythrocyte and platelet-rich areas, and their content was significantly associated (r = 0.41, p < 0.01). Thrombus TAFI was lower in patients who died during the first 3 months after stroke onset [odds ratio (OR) (95%CI); 0.59 (0.36–0.98), p = 0.043]. Likewise, we observed that thrombus MMP-10 was inversely correlated with the amount of VWF (r = −0.30, p < 0.05). Besides, VWF was associated with the presence of leukocytes (r = 0.37, p < 0.05), platelets (r = 0.32, p < 0.05), and 3 months mortality [OR (95%CI); 4.5 (1.2–17.1), p = 0.029]. Finally, plasma levels of TAFI correlated with circulating and thrombus platelets, while plasma MMP-10 was associated with cardiovascular risk factors and functional dependence at 3 months. Conclusions: The present study suggests that the composition and distribution of thrombus hemostatic components might have clinical impact by influencing the response to pharmacological and mechanical therapies as well as guiding the development of new therapeutic strategies.